2019
DOI: 10.3892/mmr.2019.10675
|View full text |Cite
|
Sign up to set email alerts
|

High‑fat treatment prevents postoperative cognitive dysfunction in a hyperlipidemia model by protecting the blood‑brain barrier via Mfsd2a‑related signaling

Abstract: Damage to the blood-brain barrier (BBB) resulting from systemic inflammation caused by surgical trauma is associated with cognitive dysfunction, and individuals with hyperlipidemia are more sensitive to such impairment. The present study was designed to ascertain whether dexmedetomidine (Dex) treatment could reduce the incidence of cognitive dysfunction following surgery in a hyperlipidemia model. Hyperlipidemia was induced in Sprague-Dawley rats (male, 6–7 months old) by consuming a high-fat diet, and rats we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 34 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…The long operation duration is coupled with factors such as postural changes of laparoscopic operation, traumatic stress, and CO 2 pneumoperitoneum. It triggers the body's sympathetic nerve excitement, increases the release of catecholamines, and causes significant stress and inflammation reactions [ 15 , 16 ]. The systemic inflammatory response that occurs under surgical trauma stress may play an essential role in the occurrence of POCD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The long operation duration is coupled with factors such as postural changes of laparoscopic operation, traumatic stress, and CO 2 pneumoperitoneum. It triggers the body's sympathetic nerve excitement, increases the release of catecholamines, and causes significant stress and inflammation reactions [ 15 , 16 ]. The systemic inflammatory response that occurs under surgical trauma stress may play an essential role in the occurrence of POCD [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that Dex can stabilize the integrity of the blood-brain barrier and reduce apoptosis. These protective effects may be mediated by reducing the activation of the NF-κB and NLRP3 inflammasome pathways ( Zhang X.P. et al, 2019 ).…”
Section: Advances In Treatmentmentioning
confidence: 99%
“…The number of patients with malignancy involved in this study was not enough to evaluate the specific subtypes of malignancies for delirium, but according to previous studies, the patients with primary or secondary CNS tumors, cancers with paraneoplastic neurological features and terminal cancers are at higher risks to develop delirium [ 31 , 32 ]; however, taking the chemotherapy medications that were reported as a predisposing factor for delirium in previous studies, were not associated with higher risks of delirium in our study. Because of the insufficient number of patients with hyperlipidemia and liver disease, we were not able to analyze these two variables; according to previous studies, hyperlipidemia plays a protective role by strengthening the blood-brain barrier, and liver diseases by disturbing plasma metabolites and electrolytes are risk factors for delirium [ 33 35 ].…”
Section: Discussionmentioning
confidence: 99%